Blockchain Governance and Teacher Empowerment to Enhance Digital Edupreneurship in the Merdeka Curriculum - Ana Theriana; Sri Wuli Fitriati; Rahayu Puji Haryani; Khatarina Rustipa; John Edwards (IAIC Bangun Bangsa, 2025)
This study focuses on the implementation of blockchain governance and teacher empowerment in the Merdeka Curriculum to enhance digital entrepreneurship in education. Although digital technology is advancing rapidly, many educators face challenges in integrating technology into their teaching processes. Therefore, the objective of this research is to examine how technology can help improve the quality of education. This study aims to explore several ways in which blockchain governance can enhance educational data management and how teachers can support the development of students' digital businesses within a more flexible curriculum. The research employs a qualitative method by conducting surveys and in-depth interviews with teachers and education administrators in Indonesia. Thematic analysis is used for qualitative data, while descriptive statistics are applied to quantitative data. The results of the study indicate that although the majority of teachers are highly interested in digital technology, they still face difficulties in implementing blockchain governance due to a lack of infrastructure and guidance. However, the Merdeka Curriculum provides teachers with the freedom to innovate in their teaching methods, which opens the door for digital education businesses. According to the discussion, blockchain governance can improve transparency in educational data management. On the other hand, teacher empowerment through technology-based training is crucial to fostering innovation in education. This study offers insights into how the application of technology and teacher empowerment are essential in creating a more innovative and effective educational ecosystem.